Cytotoxic Activity Testing The Extract of Leaves and Yellow Sirsak Fruit (Annona montana) using Method Brine Shrimp Lethality Test (BSLT) - Rahmawati, Noveri; Hari, Dewi Gulyla; Tri Nova Lovena; Nurdina Putri; Rahma Dona; Rahma Cintya Faiza; Amini, Rahmi (LPPM, Universitas Muhammadiyah Riau, 2025)
The yellow sirsak plant (Annona montana) is an annonaceae family which has been used by the community as traditional medicine properties such as treating diarrhea, vitamin C deficiency and treating boils. This study aims to determine the cytotoxic activity of the larvae of Artemia salina Leach shrimp by using the BSLT method after giving extracts from the leaves and fruit of yellow sirsak (Annona montana). The results showed that the LC50 value of the n- hexane extract of yellow sirsak leaves was 45,84 µg/mL, the ethyl acetate extract of yellow sirsak leaves was 26,44 µg/mL and the ethanol extract of yellow sirsak leaves was 13,99 µg/mL. The n-hexane extract of yellow sirsak fruit was 31,46 µg/mL, the ethyl acetate extract was 40,45 µg/mL and the ethanol extract of the yellow sirsak fruit was 19,84 µg/mL. The mixture of n-hexane leaves and yellow sirsak fruit was 29,91 µg/mL, the ethyl acetate extract mixture of yellow sirsak leaves and fruit was 21,71 µg/mL and the mixture of ethanol extract and yellow sirsak fruit was 14,75 µg/mL. Based on the research results, it can be concluded that the ethanol extract of yellow sirsak leaves shows the most active cytotoxic activity with an LC50 value of 13,99 µg/mL.